Adoption of CFLs and Electrical Lighting Usage in Pakistan - Natalie Chun; Yi Jiang (Asian Development Bank (ADB), 2012)
The widespread adoption of compact fluorescent light bulbs (CFLs) have been advocated on the premise that it will result in significant savings in electricity and reduced carbon emissions. Using a household level survey of electrical lighting and usage in Pakistan, we examine the decision to adopt CFLs and the subsequent impact of CFL adoption on electricity usage. CFL adoption is significantly influenced by variables that proxy for income and the perceived expectations about the life span of CFLs. These findings indicate that policies that educate households on the lifespan of CFLs may prove effective in increasing CFL adoption. However, the savings in electricity usage from CFL adoption is less than expected. We find that 27%–41% of potential energy savings are offset through both enlarged bulb capacity and prolonged lighting time. This behavioral response to the energy efficiency improvement therefore diminishes some of the benefits of promoting CFLs as a means to reduce energy consumption and conserve the environment.
hdl:11540/1274
Keywords: 330; Energieeinsparung; Konsumentenverhalten; Pakistan